1997
DOI: 10.1021/ic9701367
|View full text |Cite
|
Sign up to set email alerts
|

Porphyrazine Binaries:  Synthesis, Characterization, and Spectroscopy of a Metal-Linked Trinuclear Porphyrazine Dimer

Abstract: We have linked two porphyrazinedithiolates of the type Ni[pz((S-)2:R6)] (R = 4- tert-butylphenyl) by mutual chelation of a nickel ion. The trinuclear metal-linked porphyrazine dimer 9 is a monoanion, and it exhibits the classical EPR signal of Ni(III) bis(dithiolene) complexes. The absorption spectrum of the Ni(III)-linked dimer complex suggests that delocalization between the porphyrazine rings and the bridging [NiS4]- unit is significant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
82
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(86 citation statements)
references
References 36 publications
(40 reference statements)
4
82
0
Order By: Relevance
“…UV/Vis spectroscopy: Shimadzu UV-365. 1 (1), [2] bis(4-tert-butylphenyl)fumaronitrile (A), [15] 5,6-dicyano-1H-benzotriazole (B), [9] and 1-aminobenzotriazole (15) [6] were prepared as described earlier. Other chemicals and solvents were purchased from commercial sources and were used without additional purification, unless mentioned.…”
Section: Methodsmentioning
confidence: 99%
“…UV/Vis spectroscopy: Shimadzu UV-365. 1 (1), [2] bis(4-tert-butylphenyl)fumaronitrile (A), [15] 5,6-dicyano-1H-benzotriazole (B), [9] and 1-aminobenzotriazole (15) [6] were prepared as described earlier. Other chemicals and solvents were purchased from commercial sources and were used without additional purification, unless mentioned.…”
Section: Methodsmentioning
confidence: 99%
“…[268][269][270][271][272][273][274][275] For instance, asymmetric A 3 B type phthalocyanine analogues can easily form mono-or dinuclear phthalocyanine analogues 92-95 when reacted with the main-group or transition-metal ions ( Figure 6). Similarly, Ercolani and co-workers have shown that six out of eight available pyridine-type nitrogen atoms in symmetric phthalocyanine could be methylated using standard methylation agents.…”
Section: Peripheral Substituent Coordination Approachmentioning
confidence: 99%
“…56b), which is of LLCT nature. Our calculations for the monomer 1 with -tBu substituents compared with calculations performed on the octamethyl substituted [TiO-Pz] [20] indeed show that the -tBu substituents have effect over the Q band energy (Table III) has also investigated the influence of the alkyl substitution in porphyrins, stating that the substitutions may produce excitation energies downward shifts of as much as 0.2-0.3 eV. From the other side, ligand to metal charge transfer (LMCT) transitions are also expected to play a role in complexes 2-7 because of the presence of d xy orbitals into the valence region.…”
Section: Tddft Analysis: Absorption Spectramentioning
confidence: 99%
“…But owing to efficient synthetic routes reported by Fitzgerald et al [16] and Rodríguez-Morgade and Stuzhin [17], it has increased the study of their properties and applications [18][19][20][21][22][23]. Pz is constituted by four tetrapyrroles and nitrogens in position meso, and also they are called tetra-azaporphyrins.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation